Financial Distress In Indonesia: Viewed From Governance Structure - Widyaningsih, Aristanti (Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of managerial ownership, institutional ownership, the proportion of independent commissioners, the size of the audit committee, the independence of the audit committee, and the number of audit committee meetings on financial distress. There were 51 samples from 17 state-owned companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The data used are secondary data with data analysis techniques using multiple linear regression. The results showed that managerial ownership, audit committee size, and audit committee independence did not affect financial distress. While Institutional ownership, the proportion of independent commissioners, the number of audit committee meetings, and audit committee competencies affect financial distress.